A representação do argentino na (s) fronteira (s). - Militelli, Edson Matias (2016)
This theme is the result of Master thesis entitled "The representation of the Argentine in (s) Frontier (s)" in which seeks to understand the Argentine representations in space at the border and in Foz do Iguaçu from the late nineteenth century and the the twentieth century. The chosen cut back the presence of these subjects during the cycle of wood and yerba mate, the establishment the river trade and tourism to the days of the preparation of the House of Argentine them in the late 1980s to the survey, were used literature, journalism, oral and iconographic sources in order to understand the perception of these subjects at the border and the sociability. The methodology is based on qualitative research as the writings of Demo (2000) that seeks to objectify the researcher's relationship with its object directly, in which it comprises a more human and localized relationship, to take into account detailed elements from the description the sources mentioned. Although research is present in the historical focus, moves the same in other spheres of social, cultural, economic and political. The work also responds to inquiries from other areas according to the interdisciplinary aspect which divides the human know-how is one of the solutions that offer a much deeper problem, as the unity of being and knowing. Therefore, the work is important because it presents an aspect of the history of the border from the representations of this subject (Argentina) from the economic, political and cultural.